Continuous subcortical language mapping in awake glioma surgery - Axelson, Hans W.; Latini, Francesco; Jemstedt, Malin; Ryttlefors, Mats; Zetterling, Maria (Frontiers in Oncology, 2022)
Repetitive monopolar short train stimulation (STS) delivered from a suction probe enables continuous mapping and distance assessment of corticospinal tracts during asleep glioma resection. In this study, we explored this stimulation technique in awake glioma surgery. Fourteen patients with glioma involving language related tracts were prospectively included. Continuous (3 Hz) cathodal monopolar STS (5 pulses, 250 Hz) was delivered via the tip of a suction probe throughout tumor resection while testing language performance. At 70 subcortical locations, surgery was paused to deliver STS in a steady suction probe position. Monopolar STS influence on language performance at different subcortical locations were separated into three groups. Group 1 represented locations where STS did not produce language disturbance. Group 2 and 3 represented subcortical locations where STS produced language interference at different threshold intensities (≥ 7.5 mA and ≤ 5 mA respectively). For validation, bipolar Penfield stimulation (PS, 60 Hz for 3 seconds) was used as a “gold standard” comparison method to detect close proximity to language related tracts and classified as positive or negative regarding language interference. There was no language interference from STS in 28 locations (group 1) and PS was negative for all sites. In group 2 (STS threshold ≥ 7.5 mA, median 10 mA), there was language interference at 18 locations and PS (median 4 mA) was positive in only one location. In group 3 (STS threshold ≤ 5 mA, median 5 mA), there was language interference at 24 locations and positive PS (median 4 mA) was significantly (p<0.01) more common (15 out of 24 locations) compared to group 1 and 2. Despite the continuous stimulation throughout tumor resection, there were no seizures in any of the patients. In five patients, temporary current spread to the facial nerve was observed. We conclude that continuous subcortical STS is feasibly also in awake glioma surgery and that no language interference from STS or interference at ≥7.5 mA seems to indicate safe distance to language tracts as judged by PS comparisons. STS language interference at STS ≤ 5 mA was not consistently confirmed by PS which needs to be addressed.